Switching in Feedforward Control of Grip Force During Tool-Mediated Interaction With Elastic Force Fields - White, Olivier; Karniel, Amir; Papaxanthis, Charalambos; Barbiero, Marie; Nisky, Ilana (Frontiers in Neurorobotics, 2018)
Switched systems are common in artificial control systems. Here, we suggest that the brain adopts a switched feedforward control of grip forces during manipulation of objects. We measured how participants modulated grip force when interacting with soft and rigid virtual objects when stiffness varied continuously between trials. We identified a sudden phase transition between two forms of feedforward control that differed in the timing of the synchronization between the anticipated load force and the applied grip force. The switch occurred several trials after a threshold stiffness level in the range 100-200N/m. These results suggest that in the control of grip force, the brain acts as a switching control system. This opens new research questions as to the nature of the discrete state variables that drive the switching.